New and rare bivalve species for the fauna of the Kuril Islands (northwestern Pacific Ocean): A study of materials collected over 70 years of expeditions (from 1949 to 2019) - Lisitsyna, Kseniya N.; Kamenev, Gennady M. (Zootaxa, 2024)
Our study of bivalves collected during 24 marine expeditions between 1949 and 2019 at depths of 0–3,000 m off the Kuril Islands resulted in finding 16 new and 11 rare species to the fauna of this region. Their geographical and vertical distribution ranges have been significantly expanded. Species richness within the studied depths is thereby increased by 10%. Of the 27 species examined, three (Huxleyia pentadonta, Limopsis oliveri, and Samacar kurilensis) are endemic to the Kuril Islands. Photographs of shells and revised distribution data, as inferred from this study, are provided for all 27 species.